EARLY REAL-WORLD EVIDENCE FOR THE USE OF ORAL SEMAGLUTIDE IN A TERTIARY CENTRE IN MALAYSIA - Khoo, Jun Kit; Sarvanandan, Tharsini; Ooi, Ying Guat; Hee, Nicholas Ken Yoong; Lim, Quan Hziung; Lim, Lee-Ling; Vethakkan, Shireene Ratna; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION The efficacy of oral semaglutide has been well-demonstrated in the randomized controlled trials (RCT) of the PIONEER programme, but real-world evidence is lacking. We aimed to analyze the effects of oral semaglutide after six months of use in a real-world setting. METHODOLOGY In this prospective single-centre study, we analyzed the metabolic and renal outcomes of patients commenced on oral semaglutide for six months. Patients were seen in specialized diabetes clinics, and all other targets were managed according to the standard of care. RESULT A total of 177 patients were analyzed (mean age 56.3 ± 12.82 years, 46% male, mean duration of diabetes 16.2 ± 4.8 years, 38.3% had ASCVD, mean eGFR 46.3 ± 14.8 ml/min/1.73 m², 58% on insulin, 78% on SGLT2i, 67% on RAAS blockade). Baseline HbA1c, FPG, weight, BMI, and UACR were 7.91 ± 1.60%, 7.53 ± 2.78 mmol/L, 85.1 ± 21.2 kg, 33.5 ± 12.6 kg/m², and 9.8 mg/mmol (IQR 2.1–40) respectively. 80.2% tolerated semaglutide at a full dose of 14 mg daily, whilst 18.1% tolerated 7 mg daily. The discontinuation rate was 8.5%, mainly due to gastrointestinal side effects. Significant weight reduction, SBP, and HbA1c were seen with a mean difference of 3.12 kg (95% CI: 1.1–4.2, p < 0.01), 3.76 mm Hg (95% CI: 0.6–6.9, p = 0.02) and 0.31% (95% CI: 0.1–0.4, p = 0.04) respectively. FPG and UACR showed an improving trend despite missing statistical significance, FPG: –0.15 mmol/L (95% CI: –0.3–0.6, p = 0.053) and UACR: –9.8 to 7.7 mg/mmol (IQR –4.1 to –20, p = 0.19). CONCLUSION Most patients tolerated oral semaglutide at 14 mg well, with follow-up data showing significant improvement in weight, SBP, and HbA1c, comparable to that of RCTs.